Krebet Wood Craft as a Global Educational Media: The Interaction of Cultural Values and Community Empowerment - Setyaningrum, Fery; Haryanto, Eko; Ibnan Syarif, Muh.; Ponimin, Ponimin; Faozata Adzkia, Sagaf (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Objective: This study aims to analyze the role of Krebet Wood Craft as a global educational medium that not only functions as a local product, but also as a means of interaction between cultural values ​​and community empowerment. Method: This research used a qualitative method with a case study approach in Krebet Tourism Village, Bantul. Data were collected through participant observation, in-depth interviews with artisans, tourists, students, and stakeholders, document analysis in the form of archives and media publications, and focus group discussions (FGDs). Data validity was obtained through triangulation of sources and techniques. Results: Krebet Wood Craft has entered the global flow through ethnoscape (mobility of tourists, students, and researchers), mediascape (media coverage and representation), technoscape (digitalization of marketing and production innovation), financescape (global market access and creative economic opportunities), ideoscape (exchange of cultural values ​​and ideas of sustainability). Wood craft becomes a means of participatory learning based on real experience, participants not only observe, but also directly involved in the creative process (Dewey). Wood batik skills function as cultural capital that strengthens the socio-economic position of craftsmen and makes Krebet a field of multi-party interaction. Novelty: The novelty of this study lies in the integration of three theoretical frameworks within a single case study global cultural flows, cultural capital, and experiential learning with a particular emphasis on the ethnoscape dimension. This study demonstrates that the mobility of cross-cultural actors, including tourists, students, and researchers, functions not merely as context but as a key mechanism shaping learning processes and cultural exchange within Krebet Wood Craft. This integration highlights that Krebet Wood Craft is not only an artistic product, but also a dynamic cross-cultural educational medium and a model for sustainable tourism villages rooted in local culture with a global orientation.